2008
DOI: 10.1016/j.envpol.2007.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of selected PAHs from contaminated soils by rice seedlings (Oryza sativa) and influence of rhizosphere on PAH distribution

Abstract: Contributions of plant uptake and rhizosphere effect on removal of PAHs from soils are relatively insignificant. AbstractThe uptake of selected polycyclic aromatic hydrocarbons (PAHs) by rice (Oryza sativa) seedlings from spiked aged soils was investigated. When applied to soils aged for 4 months, naphthalene, phenanthrene, and pyrene exhibited volatilization loss of 98, 95, and 30%, respectively, with the remaining fraction being fixed by soil organic matter and/or degraded by soil microbes. In general, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…The uptake of phenanthrene and pyrene was subsequently accumulated in roots, or translocated to the upper part of the plants, with a portion of these chemicals becoming metabolized by the plants [50]. Su and Zhu (2008) also showed that concentrations of phenantherene and pyrene in rice roots were higher than those in shoots [51]. Previous studies indicate that PAHs, such as phenanthrene, could enter plant leaves from the atmosphere, accumulating into wax plugs of stomata, and on external surfaces of the stomatal pores, from where they enter through cuticles into the epidermis to ultimately reside on the cell walls [52].…”
Section: Distribution Of Pcb Congenersmentioning
confidence: 99%
“…The uptake of phenanthrene and pyrene was subsequently accumulated in roots, or translocated to the upper part of the plants, with a portion of these chemicals becoming metabolized by the plants [50]. Su and Zhu (2008) also showed that concentrations of phenantherene and pyrene in rice roots were higher than those in shoots [51]. Previous studies indicate that PAHs, such as phenanthrene, could enter plant leaves from the atmosphere, accumulating into wax plugs of stomata, and on external surfaces of the stomatal pores, from where they enter through cuticles into the epidermis to ultimately reside on the cell walls [52].…”
Section: Distribution Of Pcb Congenersmentioning
confidence: 99%
“…The concentration of phenanthrene and pyrene in roots had high correlation with that in rhizosphere soils extracted with DCM directly and in rhizosphere pore water (Su and Zhu 2008). Correlations for other contaminants in plant roots and external solution were also observed (Li et al 2002).…”
Section: Discussionmentioning
confidence: 78%
“…The contribution of root uptake for PAHs was only 2.4% in soil spiked with naphthalene, phenanthrene, and pyrene (Su and Zhu 2008). The PAHs in shoot were considered to accumulate from atmosphere directly other than transport from root (Su and Zhu 2008;Keyte et al 2009 Table 5 The loading matrix of partial least squares regression models for oat dissipation in rhizosphere soil was due to biodegradation or biotransformation (Binet et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Controversial results, either increased or decreased the biomass of plant seedlings under PAH stress, have also been reported previously ( Kummerova and Kmentova 2004;Su and Zhu 2008;Sverdrup et al 2003). Root activity (determined by root dehydrogenase activity) is an important physiological and biochemical index of plant health and is related to the metabolic ability of plants (Zhao et al 2011).…”
Section: Physiological Responses Of Two Rice Cultivars To Pah Stressmentioning
confidence: 83%
“…Recently, increased amounts of residual PAHs have been detected in agricultural soils, such as paddy field, due to industrial processes, vehicle emissions, waste incineration, and biomass burning (Ping et al 2007;Su and Zhu 2008;Tao et al 2004). This has attracted increasing public concern since they are highly persistent to deplete and have toxic properties of carcinogenicity, teratogenicity, and mutagenicity (Ma et al 2010a).…”
Section: Introductionmentioning
confidence: 99%